Compatibilizing effect of maleic anhydride on the mechanical properties of Mengkuang leaves fibre reinforced polythylene composites - Siregar, J. P. (2017)
The performance of Mengkuang Fiber or Pandanus Tectorius reinforced polyethylene composites with different fiber volume and different mesh size, were studied. Experiments that based on the different volume fiber are 10%, 20%, and 30% of fiber while for different size of fiber are <0.5 mm, 0.5-1 mm, and 1-2 mm. The purpose of this study was to fabricate the natural fiber reinforced composites using Mengkuang fiber and low density polyethylene with different fiber weight, different fiber length, and different MAPE percentage. The mechanical properties of the fabricated composite were investigated. The process involved in this project were extrusion process and hot compress process. The extrusion process was done by using the temperature set up to 168º C, 168ºC, 165ºC, 165 ºC, and 162, 163 º C according to zone 1, 2, 3, 4, 5 and 6 with 60rpm screw speed. Hot and cold compressed machine used to compress the compound pellet where the pressure was set minimum 8 MPa to maximum 10 MPa with the temperature was 165 degree celcius. The mechanical testing performed were impact and flexural test according to ASTM standards D790-10 and Izod D256 standard test. The flexural test were performed using Universal Testing Machine and the impact test were performed using Impact Testing Machine. The dimension of the specimens prepared for flexural test was 12.7cm x 1.27cm x 0.3 cm whereas the dimension for impact test specimens was 6.4cm x 1.27cm x 0.3 cm. Seven specimens was prepared for all composition of composites. From the result and discussion presented, the addition of Mengkuang fiber to LDPE increased the flexural modulus, flexural strength, for different volume fiber, different size fiber, and different MAPE percentage the addition of Mengkuang fiber to LDPE increased the flexural modulus, flexural strength, for different volume fiber and different size fiber. The impact strength shows the decrease with different volume and different MAPE percentage. The increase in the strength and modulus of the Mengkuangfiller composites indicates the increasing in the rigidity of polyethylene due to the mobility limitation in polyethylene matrix that contain Mengkuang fiber. When the modulus is increasing with the increasing of fiber loading of Mengkuang fiber, the stress transfer across the polymer particles interface prevented the movement around each particle led to overall increase in modulus and strength. The higher filler amount in the polyethylene and Mengkuang-filler composites resulted in stiffening and hardening of the composite thus reduced its resilience and toughness and possess low impact energy. Fiber length also affected the properties of Mengkuang fiber where Mengkuang fiber with longer length could withstand a high load and tolerate more stress than shorter ones led to high flexural strength and modulus.